Towards the ’Verified Verifier’. Theory and Practice - D. A. Kondratyev; A. V. Promsky (Моделирование и анализ информационных систем, 2014)
As opposed to traditional testing, the deductive verification represents a formal way to examine the program correctness. But what about the correctness of the verification system itself? The theoretical foundations of Hoare’s logic were examined in classical works, and some soundness/completeness theorems are well-known. However, we practically are not aware of implementations of those theoretical methods which were subjected to anything more than testing. In other words, our ultimate goal is a verification system which can be self-applicable (at least partially). In our recent studies we addressed ourselves to the metageneration approach in order to make such a task more feasible.